RANCANG BANGUN MESIN SPOT WELDING AND SOLDERING IRON SEMI PORTABLE - Hidayat, Achmad Fachrus; Sakti, Arya Mahendra (Universitas Negeri Surabaya, 2022)
In the welding process, there are still some obstacles, such as the process is long and the results are not neat. In addition, a tool that can be used as a solder is needed which aims to support the repair process. To overcome this we need a tool with the best method, the author chose to develop a spot welding machine as the method. The spot welding design also combines stationary and portable types so that it can be used for purposes with different conditions. This design aims to find out the best design, control system, tool manufacturing process, and optimal operating method. Tool design begins with determining the design method. Design methods include: determining the theme, observation, Identification of Tool Requirements (Specifications), design concepts and design methods. The results of the design obtained tool specifications including: In the design of this spot welding machine using a MOT (Microwave Oven Transformer) transformer with a power of 1,215.35 Watt. So that the electric charge that flows on this machine for 10 seconds is 11,073 Joule. The control system used is based on a timer. The welding cable used is NYAF (fiber) type cable with 16mm. The arm drive system (JIG) uses a pressure cylinder mechanism that is actuated by a pedal. Inside the compression cylinder there is a spring with specifications 16mm, 15mm long with a wire diameter of 1.5mm which is used to generate welding pressure. The combination of the pedal mechanism and the spring obtained a pressure of 0.35 bar. The tool testing process is carried out by connecting a nickel plate that has a thickness of 0.5mm with a width of 5mm. The current given when the welding process is 390 Ampere with a pressure of 0.35 bar. Can be concluded; The best welding results occur in the time range between 4-6 seconds.